2010
DOI: 10.1007/s12072-010-9180-8
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of prognostic factors for patients with hepatorenal syndrome in a tertiary center

Abstract: Introduction Hepatorenal syndrome (HRS) is one of the serious complications in patients with advanced cirrhosis and ascites. In tertiary centers, most patients were classified as having type 1 HRS for their rapid progressive diseases. However, no significant predictors have been assessed previously for patients with type 1 HRS. In addition to the initial model of end-stage liver disease (MELD) scores and biochemistry parameters, we want to further investigate the prognostic importance of changes in MELD scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…These results are opposed to a large body of evidence showing that liver function parameters are the main mortality predictors in hepatorenal syndrome. A study by Yang et al showed that serum bilirubin, albumin, creatinin and MELD score were significantly associated with prognosis of patients with hepatorenal syndrome 20 . In our study, in contrast to the above papers, the results of univariate regression analysis suggest that parameters of liver function (total bilirubin, albumin, INR, MELD and MELD-Na score) as well as age, serum and urine sodium and creatinine are significant predictors of hepatorenal syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…These results are opposed to a large body of evidence showing that liver function parameters are the main mortality predictors in hepatorenal syndrome. A study by Yang et al showed that serum bilirubin, albumin, creatinin and MELD score were significantly associated with prognosis of patients with hepatorenal syndrome 20 . In our study, in contrast to the above papers, the results of univariate regression analysis suggest that parameters of liver function (total bilirubin, albumin, INR, MELD and MELD-Na score) as well as age, serum and urine sodium and creatinine are significant predictors of hepatorenal syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in HRS determined some prognostic markers as predictors of mortality including serum creatinine, low urine sodium, advanced age, MELD score and Cystatin C among others . To our knowledge, role of serum and/or urine NGAL has been assessed as a prognostic marker in patients with HRS in only one recent study .…”
mentioning
confidence: 99%
“…The International Ascites Club met in 2007 and set up a consensus on a new definition, diagnostic criteria and recommendation for the treatment of HRS . HRS is divided into two types: type 1 and type 2 HRS [2,3] . Type 1 HRS is typified by rapid deterioration of renal function as defined by a rising of serum creatinine level to over 2.5 mg/dL in less than 2 wk, and is characteristically presented as AKI [2][3][4][5] .…”
Section: Definition and Types Of Hepatorenal Syndromementioning
confidence: 99%
“…HRS is divided into two types: type 1 and type 2 HRS [2,3] . Type 1 HRS is typified by rapid deterioration of renal function as defined by a rising of serum creatinine level to over 2.5 mg/dL in less than 2 wk, and is characteristically presented as AKI [2][3][4][5] . Type 2 HRS runs a slower progressive clinical course with a median survival of 6 mo, and is classically associated with refractory ascites .…”
Section: Definition and Types Of Hepatorenal Syndromementioning
confidence: 99%
See 1 more Smart Citation